Rejoicing urban spaces for interaction enhancement - Zulkarnain, Nurnabilah; Abu Bakar, Aniza; Ab Sani, Jasasikin (Department of Landscape Architecture, KAED, IIUM, 2024)
Interactive landscapes in urban settings contribute to significant benefits, primarily targeting human-with-human interaction, human-with-nature interaction, and nature-the-surrounding interaction which is the key to enhancing the overall quality of life, and tackling urgent environmental issues. In many urban areas, the problem of insufficient engagement and interaction between people and the natural world is on the rise. This scarcity of green spaces, limiting opportunities to escape the concrete urban environment and reconnect with nature, tends to lead to social isolation and contributes to the adverse impact on the physical and psychological well-being of the people. This study which took place in Danau Kota, Kuala Lumpur, Malaysia, implements a mixed-methods approach, integrating both qualitative and quantitative data. The utilised techniques consist of document analysis, site inventory, and analysis by employing an observation approach, survey questionnaires, and semi-structured interviews. Based on the analysis, the results indicate the potential for enhancing open spaces to become highly interactive. Design strategies are formulated to enhance interactivity.